Pengaruh Kualitas Auditor, Leverage, Harga Saham, Inflasi, Capital Expenditure Terhadap Manajemen Laba Pada Perusahaan Manufaktur yang Terdaftardi BEI - Annisa Silfiana; Diana Dwi Astuti; Wiwik Fitria Ningsih (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2020)
This study aims to determine the effect of Audit Quality, Leverage, Stock Prices, Inflation, Capital Expenditure, on earnings management as measured by discretionary accruals. In agency theory, agency problems arise because of the opportunistic behavior of the agent, namely the behavior of management to maximize their own well-being that is contrary to the principal's interests. Managers have the urge to choose and implement accounting methods that can show good performance to get bonuses and principals, the choice of methods deliberately chosen by management is known as earnings management.This type of research is an empirical study. The study was conducted on cigarette manufacturing sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. Data obtained through documentation, by collecting annual report data and company financial reports on the Indonesia Stock Ecchange (IDX) web. Data regarding discretionary accruals to measure earnings management, dummy to measure auditor quality, debt equity ratio to measure leverage, earnings per share to measure stock prices, inflation at certain periods to measure inflation, capex ratio to measure capital expenditure and tested using regression tests linear regression with the help of SPSS analysis.The results of this study indicate that audit quality and leverage significantly influence earnings management while the other three variables are stock price, inflation, capital expendiure, and no effect on earnings management.